Trends in pancreatic cancer mortality in Europe, 1955-1989 - E. Fernandez; M. Porta; F. Lucchini; F. Levi; C. La Vecchia; E. Negri (International Journal of Cancer, 1994)
Trends in death certification rates from pancreatic cancer over the period 1955-1989 were analyzed for 25 European countries (excluding the former Soviet Union and a few smaller countries). In 1985-1989, rates for males ranged between 5.3/100,000 (age-standardized world population) in Spain and 10.3/100,000 in Hungary and Czechoslovakia. Other high-mortality areas were located in Northern Europe (Finland, Iceland, Ireland, Denmark) and Central Europe (Austria, Poland, Germany), whilst mortality was lower in Southern Europe (Portugal, Greece). Between 1955 and 1989, mortality rates increased in all the countries considered, the change ranging between 6% in Scotland and 279% in Spain; the rises were higher in the Mediterranean and Eastern European countries than in Northern Europe. Among females, Nordic countries such as Iceland, Sweden and Denmark had the highest mortality rates in 1985-1989 (over 6/100,000) and, as for males, Southern Europe (Spain, Portugal, Greece) appeared as a low-mortality area (around 3/100,000). During the 1955-1989 period, upward trends were observed in all the countries studied, with the highest increase in Greece, Italy, Bulgaria, Poland and Spain. A negative correlation was observed between the percent change in mortality rates between 1955-1959 and 1985-1989 and the rate in 1955-1959 among both males (r = -0.95, p < 0.001) and females (r = -0.81, p < 0.001). Thus, a systematic levelling of rates was observed in most countries, with the exception of the UK and some Nordic countries, whose rates were already high in the late 1950s. Tobacco smoking and dietary factors could account for some of the generalized upward trends. Improved diagnostic and death certification of the disease might also partially explain the observed figures.